Coup‐Proofing and Beyond: The Regime‐Survival Strategies of Hugo Chávez. (6th November 2017) - Martin, Heather
Abstract : After a long history of domestic political and economic instability, rampant corruption, and income inequality, former Venezuelan President Hugo Chávez entered the political arena in 1998, touting a campaign for change. After winning the presidency by a landslide in 1999, Chávez began to implement a series of policies that changed Venezuela forever. The elimination of presidential term limits was perhaps one of the most‐controversial moves that Chávez made during his presidency. Despite significant backlash from the Venezuelan population and protest by the opposition, Chávez remained in office for almost 14 years. This article explores the Chávez presidency from 1999–2013, concluding that his political longevity can be attributed to a series of regime‐survival strategies and coup‐proofing techniques implemented during his time in office.